Immune response and severity of Omicron BA.5 reinfection among individuals previously infected with different SARS-CoV-2 variants - Li, Lu; Xie, Zhiwei; Li, Youxia; Luo, Minhan; Zhang, Lieguang; Feng, Chengqian; Tang, Guofang; Huang, Huang; Hou, Ruitian; Xu, Yujuan; Jia, Shijie; Shi, Jingrong; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction COVID-19 continues to spread worldwide, with an increasing number of individuals experiencing reinfection after recovering from their primary infection. However, the nature and progression of this infection remain poorly understood. We aimed to investigate the immune response, severity and outcomes of Omicron BA.5 reinfection among individuals previously infected with different SARS-CoV-2 variants. Methods We enrolled 432 COVID-19 cases who had experienced prior infection with the ancestral SARS-CoV-2 virus, Delta variant or Omicron BA.2 variant between January 2020 and May 2022 in Guangzhou, China. All cases underwent follow-up from March to April, 2023 through telephone questionnaires and clinical visits. Nasal lavage fluid and peripheral blood were collected to assess anti-RBD IgA, anti-RBD IgG and virus-specific IFN-γ secreting T cells. Results Our study shows that 73.1%, 56.7% and 12.5% of individuals with a prior infection of the ancestral virus, Delta or Omicron BA.2 variant experienced reinfection with the BA.5 variant, respectively. Fever, cough and sore throat were the most common symptoms of BA.5 reinfection, with most improving within one week and none progressing to a critical condition. Compared with individuals without reinfection, reinfected patients with a prior Delta infection exhibited elevated levels of nasal anti-RBD IgA, serum anti-RBD IgG and IFN-γ secreting T cells, whereas there was no noticeable change in reinfected individuals with a prior BA.2 infection. Conclusion These results suggest that BA.5 reinfection is common but severe outcomes are relatively rare. Reinfection with a novel SARS-CoV-2 variant different from the prior infection may induce a more robust immune protection, which should be taken into account during vaccine development.